Competências socioemocionais na educação profissional: requisito para a formação integral dos estudantes do IFAP - FERREIRA, Ricardo Batista (2023)
This study is based on recent Brazilian Educational Policies, which began to require the inclusion of socio-emotional skills in Professional and Technological Education (EPT). From these prerogatives, the need arises to restructure curricula and reorganize pedagogical spaces, which need to encompass cognitive and socio-emotional skills in a significant way. Modifying curricula with the inclusion of socio-emotional skills needs to provide students with integral (omnilateral) human training. In EPT, technical-professional knowledge needs to go beyond content training, preparing students to face real situations in their future profession. Adult life, and life at work, require behaviors and knowledge that students and teachers will use in their social and professional practices, inside and outside the school environment. In view of the changes, this research had the general objective of analyzing the meanings and meanings of the perceptions of teachers and students at the Federal Institute of Amapá (IFAP), Macapá and Santana campuses, about the socio-emotional skills necessary for qualitative training in Professional Education. To support the discussion of political aspects, the General National Curricular Guidelines for Professional and Technological Education were used - CNE/CP Resolution No. 1, of January 5, 2021, in the National Common Curricular Base for Basic Education (BNCC, 2017) and National Common Curricular Base for Secondary Education (BNCC -EM, 2018). Thus, the study of socio-emotional skills was developed within the scope of the Professional Master's Degree in Professional and Technological Education (ProfEPT), in the line of research Organization and Memories of Pedagogical Spaces in EPT and was constructed from a mixed approach, using qualitative research and quantitative, of an applied and exploratory nature, based on literature review procedures. As a data collection instrument, we used questionnaires, constructed from the Socio-Emotional Competence Scale (CSE). In summary, it was found that socio-emotional skills exist quite frequently and are used to intervene assertively in socio-professional life situations, with a positive result prevailing. Despite the frequency of dominance, some variables signal the need for better development. Both teachers and professors signaled the importance of including this knowledge in their training. Although these skills are relevant in the social, educational, professional context and in the world of work, they also play a fundamental role in the complexity of the contemporary world, enhancing the mental and emotional health of students and teachers, and enabling significant improvements in academic performance and interpersonal relationships. Therefore, as a result of the research, the Educational Product (EP) was constructed in the format of a teaching guide, with theoretical-methodological concepts to assist teachers, contributing to the dissemination of ideas and practical possibilities for developing socio-emotional skills. 13 EPT teachers evaluated the guide and meets its objective, with an agreement rate of 92.3% and 100%, in the items referring to the three categories of analysis: conceptual, pedagogical and communicational.